A comparison of family health history of breast cancer, colorectal cancer, and diabetes in self-reported survey and electronic health records data, All of Us Research Program - Ridgely Fisk Green; Ramal Moonesinghe; Sun Hee Rim; Katherine Kolor; Danielle Rasooly; Kevin Littrell; Scott Bowen; W. David Dotson; Muin J. Khoury (Genetics in Medicine Open)
Purpose: We used data from the All of Us Research Program to examine sociodemographic differences in family health history (FHH) survey access, availability of electronic health records (EHR) data, FHH knowledge, FHH in the survey and EHR data, and concordance of FHH in survey and EHR data for breast cancer, colorectal cancer, and diabetes. Methods: We calculated percentages and standard errors of participants who accessed the FHH survey, reported no FHH knowledge, had EHR data available, had FHH data in the survey and EHR, and had FHH in the survey or EHR that was not captured in the other data source for breast cancer, colorectal cancer, and diabetes. We stratified by age, race and ethnicity, sex, sexual orientation, household income, employment status, education level, marital status, and health insurance status. To determine significant differences, we calculated absolute and relative disparity, Z-tests, and P values with the significance threshold adjusted for multiple comparisons using the Bonferroni correction. Results: We found significant disparities in accessing the survey and reporting no FHH knowledge across almost all sociodemographic subgroups. Most FHH reported in the survey was not captured in the EHR data, most significantly for participants who were aged 20 to 29, were students, did not graduate high school, were never married, or had no health insurance. Conclusion: Our study showed significant sociodemographic disparities in FHH survey access, FHH knowledge, and FHH captured in EHR structured data, which could widen inequities in access to FHH-based interventions.